Enkulturasi Alat Musik Bundengan di SMP Negeri 2 Selomerto Wonosobo - Helena Evelin Limbong (Universitas Negeri Medan, 2019)
The enclosure process of bundengan musical instruments that took place at Selomerto Wonosobo 2 JuniorHigh School as an effort to inherit traditional arts to the next generation. The inheritance of bundenganmusical instruments at the school includes elements of enculturation and the process of socializationthrough educational facilities. The efforts of enculturation of bundengan musical instruments in WonosoboSelomerto 2 Middle School were actualized through various activities. The support and role of appreciationfrom the community and government institutions in collaboration with SMP Negeri 2 Selomerto in reintroducing the use of bundengan musical instruments in ceremonial and ceremonial events provides spacefor appreciation and fulfillment of students' needs for their existence, the existence of musical instruments,schools and students and the community. The use of social media, and print media, is one of the culturaltransmission media in informing and becoming a form of internalization. This research is qualitativeresearch, which is carried out using survey methods; observations, in-depth interviews (independentinterviews), documentation, and literature studies that refer to the concept of cultural enculturation.